Tomáš Baťa's Methods in Contemporary Management - Kubová, Kateřina (2020)
Tomáš Baťa dramatically changed the global shoe industry by creating hundreds of innovative advancements in shoe design, manufacturing processes and employee work conditions with his paradigm breaking a socially conscious approach. His ideas and activities are said to be valuable not only in his era but also nowdays, for future generations. This thesis aims to answer the question whether Tomáš Baťa's managerial methods are applicable in contemporary management in the world but also in the Czech Republic. The research shows that some methods, for example building complex city are used nowdays by China, even though motivation to build them differs and that employee care and education is getting more important than ever. On the other hand, some procedures like for example providing accomodation or intervention into private life of employees seem quite obsolete.